Utilization of Galvanic Sludge as Raw Material for Production of Glass - Ozdemir, Ozgul Dere; Figen, Aysel Kanturk; Piskin, Sabriye (INT ASSOC COMPUTER SCIENCE & INFORMATION TECHNOLOGY PRESS-IACSIT PRESS, 2011)
Galvanic sludge is a filter press cake that generated at the end of the waste water treatment process. It is very dangerous to human health and environment due to high heavy metal concentration. Treatment sludge of Bergama-Ovacik Gold Mine treatment plant is generated from waste water treatment process like galvanic sludge. High content of SiO2 of this waste. makes it desirable glass network former additive. In this study, vitrification of galvanic sludge was investigated by using gold mining treatment sludge, H3BO3 and Na2CO3. For this purpose, the effect of 10% and % 20 galvanic sludge additives on vitrification properties was determined by X-Ray Difractometer (XRD) and Fourier Transform Infrared Spectrometer (FT-IR) instruments and Toxicity Characteristic Leaching Procedure (TCLP) Analysis method.
Keywords: Galvanic sludge; glass; vitrification; boron; characterization; LEVEL RADIOACTIVE-WASTE; INDUSTRIAL-WASTES; CERAMICS; BEHAVIOR; METALS; OXIDE; Engineering